Dielectric properties of Ga2O3-doped barium iron niobate ceramics - Sanjoom,K. (Wiley-VCH Verlag, 2015)
Ga-doped BaFe0.5Nb0.5O3 (Ba(Fe 1-xGax)0.5Nb0.5O3) ceramics were fabricated and their properties were investigated. All ceramics showed perovskite structure with cubic symmetry and the solubility of Ga in BFN ceramics had a limit at x = 0.2. Examination of the dielectric spectra indicated that all ceramic samples presented high dielectric constants that were frequency dependent. The x = 0.2 ceramic showed a very high dielectric constant (εr > 240 000 at 1 kHz) while the x = 0.4 sample exhibited high thermal stability of dielectric constant with low loss tangent from room temperature (RT) to 100°C with εr > 28 000 (at 1 kHz) when compared to other samples. By using a complex impedance analysis technique, bulk grain, grain boundary, and electrode response were found to affect the dielectric behavior that could be related to the Maxwell-Wagner polarization mechanism © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.